Identifikasi Dan Uji Daya Hambat Isolat Bakteri Endofit Bunga Tanaman Cengkeh (Syzygium aromaticum L.) Terhadap Bakteri Patogen - Citra Sepriana; Eti Sumiati; Dwi Soelistya Dyah Jekti; Lalu Zulkifli (Jurnal Penelitian Pendidikan IPA, 2020)
This research was conducted to find out the capabilities of endophytic bacteria isolated from flowers of the clove plants in inhibiting the growth of bacteria Streptococcus mutans, Staphylococcus aureus, Klebsiella pneumoniae and Escherichia coli and to identify endophytic bacteria that potensial to produce an antibacterial. Stages of this research include the isolation of endophytic bacteria from flowers of the clove plants, antibacterial test, and molecular identification based on 16S rRNA. Isolates of endophytic bacterial of clove plants flower produce 5 isolates, 4 isolate inhibited the bacteria S. aureus. Based on 16S rRNA molecular identification, endophytic bacterial isolates of clove plants flower which have inhibitory closely related to Bacillus amyloliquefasiens, Staphylococcus epidermidis 1034 MPA and Bacillus cereus JL.